Preparation of nano zinc oxide, its characterisation and use in styrene butadiene rubber - Begum, P.M.S. (2023)
Zinc oxide (ZnO) of nanometer particle size was prepared by precipitation and solid state pyrolytic method. TEM, XRD and the surface area studies showed that zinc oxide prepared in the laboratory has a particle size in the nanometer range and a high surface area. This nano zinc oxide was used as an activator in non-polar synthetic rubber compounds. The cure characteristics and mechanical properties were compared with that containing conventional zinc oxide. It is found that a low dosage of zinc oxide was enough to give equivalent curing and mechanical properties compared to the one containing a higher dosage of conventional zinc oxide.